The Head-Mounted Displays (HMDs): Towards a Playful Approach to Architectural Space - Sami Kamoun (ARCHive-SR)
This study explores the use of head-mounted displays (HMDs) as augmented fabrication interfaces within the fields of architecture and landscape design. It focuses on the analysis of Augmented Grounds, a landscape installation designed by Soomeen Hahm, Jaeheon Jung, and Yumi Lee.